An assessment of new character in hoverfly species delimitation using linear and geometric morphometrics – genus Merodon Meigen, 1803 (Diptera: Syrphidae) as a case study - Jelena Ačanski; Tamara Tot; Ana Grković; Marija Miličić; Snežana Radenković; Ante Vujić (European Journal of Taxonomy, 2023)
Detection of morphologically indistinguishable cryptic species implies using an integrative taxonomic approach with a combination of molecular, contemporary morphological, ecological and other relevant analyses. Within a contemporary morphological analysis, two approaches are commonly used in hoverfly taxonomy: a geometric morphometric analysis of the wing and surstyle shape. Here, the importance of the R4+5 vein shape is tested in cryptic species delimitation within four Merodon species groups using linear and semilandmark geometric morphometric analyses. As expected, geometric morphometrics showed a stronger resolution compared to linear morphometrics. Linear morphometrics failed to detect differences related to sexual dimorphism or differences among the species M. pruni and M. obscurus. However, all cryptic species and sexes were separated with high significance based on the R4+5 vein shape. Moreover, obtained results concurred with the landmark-defined wing shape and molecular results published in previous studies. Additionally, combining two characters, the semilandmark R4+5 vein shape and the landmark-defined wing shape, provided more detailed and precise insights into the shape differences. Our results showed that the R4+5 vein shape stands out as an important character in species delimitation of hoverflies where the sinuation of this vein is present. Therefore, it can be beneficial as a single character or in combination with a landmark-based wing shape analysis.